Uniformly Asymptotic Stability of Positive Almost Periodic Solutions for a Discrete Competitive System - Qinglong Wang; Zhijun Liu (Journal of Applied Mathematics)
This paper is devoted to the study of almost periodic solutions of a discrete two-species competitive system. With the help of the methods of the Lyapunov function, some analysis techniques, and preliminary lemmas, we establish a criterion for the existence, uniqueness, and uniformly asymptotic stability of positive almost periodic solution of the system. Numerical simulations are presented to illustrate the analytical results.